Initial Psychometric Evaluation of the Inventory of Parent and Peer Attachment in Greek Adolescents - Georgios Giannakopoulos; Aikaterini Fostini; Renati Marinou; Varvara Salavou (European Journal of Investigation in Health, Psychology and Education, 2026)
Adolescents’ perceived security in relationships with parents and peers relates to psychosocial adjustment, yet the psychometric performance of the Inventory of Parent and Peer Attachment (IPPA) has not been examined in Greece. This study evaluated the Greek IPPA in a non-probability sample of 432 adolescents aged 12–16 years from five schools in Attica (Greece). Internal consistency, item-level analyses, floor and ceiling effects, and one-factor, two-factor, correlated three-factor, and bifactor models were examined using ordinal WLSMV estimation. Relations with Strengths and Difficulties Questionnaire scores were assessed. Parent Total Security and Peer Total Security showed high internal consistency (α = 0.94 and 0.93, respectively; ω = 0.94 for both). The correlated three-factor model showed acceptable fit for the parent form and weaker fit for the peer form, while Trust and Communication were highly correlated in both forms. Bifactor indices indicated substantial general-factor saturation, although the specific Trust factors were poorly defined. Higher total security scores were associated with fewer psychosocial difficulties. Overall, the parent and peer total scores appear more defensible than the separate subscales for preliminary, group-level descriptive use in similar samples, whereas subscale interpretation, particularly distinctions between Trust and Communication, should remain cautious. These findings require independent replication and do not support individual clinical decision-making or the identification of attachment classifications, attachment disorders, or disorganization.